82-115=-8(-4y)-17(2y)+y

Simple and best practice solution for 82-115=-8(-4y)-17(2y)+y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 82-115=-8(-4y)-17(2y)+y equation:


Simplifying
82 + -115 = -8(-4y) + -17(2y) + y

Combine like terms: 82 + -115 = -33
-33 = -8(-4y) + -17(2y) + y

Remove parenthesis around (-4y)
-33 = -8 * -4y + -17(2y) + y

Multiply -8 * -4
-33 = 32y + -17(2y) + y

Remove parenthesis around (2y)
-33 = 32y + -17 * 2y + y

Multiply -17 * 2
-33 = 32y + -34y + y

Combine like terms: 32y + -34y = -2y
-33 = -2y + y

Combine like terms: -2y + y = -1y
-33 = -1y

Solving
-33 = -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-33 + y = -1y + y

Combine like terms: -1y + y = 0
-33 + y = 0

Add '33' to each side of the equation.
-33 + 33 + y = 0 + 33

Combine like terms: -33 + 33 = 0
0 + y = 0 + 33
y = 0 + 33

Combine like terms: 0 + 33 = 33
y = 33

Simplifying
y = 33

See similar equations:

| 8x-.2=9.8 | | 80x+40=84x | | Y-8=4(x-5) | | -4i= | | 5x+(-4y)+(-15x)+6y= | | 64+a^6= | | 2y+4x=-1 | | -(2x-5y)= | | 9(2x+10)-7x*4= | | 7(5a+3b)+7(2a+4b)= | | x-18=-1-10 | | -5(4p+3)-31=2(5p+7) | | 8a^3-1= | | 3(3x-9)-2=3(x-5)+16 | | h/15=-7 | | (4x+5)6= | | 4-8n+3n=8-99 | | 9659-268(6)=8262 | | -49+7y+6=2(5y-4)-8 | | 3.2x=-9.6 | | 9[6-(-9x-4)]=729x+378 | | -2x-y=-16 | | -2(x+4)=2x+4 | | 2(-x+3x)3(-x)+7=(-x)+(-3) | | x=x+6.48 | | (2x^3+7)(2x^3+6)= | | 9(c-5)+8=5+c-42 | | m-7m+9m+7= | | 4x-3=-2x+7+8x | | x^2+y^2+8x-8y-49=0 | | 5c-4c+1c= | | (X+1)(x+1)=-2x |

Equations solver categories